2004
DOI: 10.1128/aac.48.5.1733-1738.2004
|View full text |Cite
|
Sign up to set email alerts
|

Trypanocidal Activity of Melamine-Based Nitroheterocycles

Abstract: A series of nitroheterocyclic compounds were designed with linkages to melamine or benzamidine groups that are known substrates of the P2 aminopurine and other transporters in African trypanosomes of the brucei group. Several compounds showed in vitro trypanotoxicity with 50% inhibitory concentrations in the submicromolar range. Although most compounds interacted with the P2 transporter, as judged by their ability to inhibit adenosine transport via this carrier, uptake through this route was not necessary for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 40 publications
(53 reference statements)
3
55
0
1
Order By: Relevance
“…The ability of these compounds to interact with the P2 transporter was assessed using the well-established oil-stop method to measure tritiated adenosine (0.05 M) uptake via that transporter in the presence of a range of concentrations (0.1 mM to 100 nM) of each inhibitor. In general the compounds were found to have high affinities for the P2 transporter (Table 1), of the same magnitude as the transporter's natural substrate adenosine, and generally around an order of magnitude higher than the affinities of a series of novel melamine-carrying compounds (1,14,18,19). This could indicate a structural preference for the benzamidine group in P2 interactions, and, this being the case, future compounds developed as potential P2- selective trypanocides could benefit from carrying a benzamidine residue.…”
mentioning
confidence: 99%
“…The ability of these compounds to interact with the P2 transporter was assessed using the well-established oil-stop method to measure tritiated adenosine (0.05 M) uptake via that transporter in the presence of a range of concentrations (0.1 mM to 100 nM) of each inhibitor. In general the compounds were found to have high affinities for the P2 transporter (Table 1), of the same magnitude as the transporter's natural substrate adenosine, and generally around an order of magnitude higher than the affinities of a series of novel melamine-carrying compounds (1,14,18,19). This could indicate a structural preference for the benzamidine group in P2 interactions, and, this being the case, future compounds developed as potential P2- selective trypanocides could benefit from carrying a benzamidine residue.…”
mentioning
confidence: 99%
“…We previously reported (11,17) that the melamine nitrofuran WSP934 has very potent activity against T. brucei rhodesiense STIB 900, with a 50% effective concentration (EC 50 ) of about 11 nM, which is around the same order as that of melarsoprol (6 nM), a currently licensed drug. For comparison, the EC 50 of nifurtimox is 1.5 M. This compound is a nitrofuran registered for use against Chagas' disease and, in combination with eflornithine, to treat human African trypanosomiasis (2).…”
Section: Resultsmentioning
confidence: 98%
“…One of these molecules, our initial lead, WSP934 ( Fig. 1) (compound 3a in Stewart et al [17]), was found to be curative of a rodent model of HAT (11,12,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…73 A estratégia empregada neste trabalho envolveu o acoplamento do grupo melamina (fração de reconhecimento estrutural P2) a nitro-heterocíclicos, levando em consideração alguns requerimentos importantes para a absorção através do transportador P2, incluindo um grupo amidino, um anel aromático e um heteroátomo eletronegativo. Entre as características estruturais marcantes do composto líder da série (53), 74 pode-se destacar a presença de um grupo nitro, um fragmento triazina contendo o sistema amidínico, dois aneis aromáticos, heteroátomos e a presença da função hidrazona na fusão dos fragmentos de triazina e do anel contendo o grupo nitro, como pode ser observado na Figura 13.…”
Section: Planejamento De Moléculas Bioativas: Integração Entre Químicunclassified